Non-psychotic psychiatric disorders in patients with chronic somatic non-communicable diseases under conditions of permanent stress: The role of metabolic therapy - Chaban, Олег; Khaustova, Олена; Tymoshchuk, Євген (Psychosomatic Medicine and General Practice, 2023)
Abstract. The article discusses the current issues of comorbidity between mental disorders and chronic non-infectious somatic diseases, highlighting the importance of a multidisciplinary patient-centered approach in the treatment of these conditions. Additionally, in light of the negative impact of the Russian military aggression on the mental health of Ukrainians, this paper presents the positive experience of using the dietary supplement Cognitium® in a regimen of 1 ampule twice a day as an additional therapy for non-psychotic mental disorders in adult patients with chronic somatic diseases under conditions of chronic stress. The positive impact of Cognitium® was noted in the reduction of affective, cognitive and somatoform symptoms, specifically: decreasing in the level of anxiety and depression, mood stabilization, improvement of concentration and memorization of new information, increasing energy levels, restoration of sleep and appetite.